The Phantom Tollbooth - Juster, Norton; Feiffer, Jules (London; HarperCollins children's books, 2008)
Bored and restless, Milo never expects much from life$1 (Buntil a mysterious tollbooth appears in his room. Driving through it, he enters a magical world of talking watchdogs, word markets, and number mines. On a quest to rescue two princesses, Milo discovers that learning can be the greatest adventure of all.s
Keywords: English fiction